In vitro cytotoxic efficacy of PEG encapsulated manganese-doped zinc oxide nanoparticles on hepatocellular carcinoma cells. (10th November 2019) - Vijayakumar, G.; Boopathi, G.; Elango, M.
ABSTRACT: The present study investigates the in vitro cytotoxic efficacy of polymer encapsulated bare and Mn-doped ZnO nanoparticles against human liver carcinoma Huh7 cell lines. PEG capped bare and Mn (2.0, 2.5 and 3.0 wt%) doped ZnO nanoparticles were synthesised through chemical precipitation method. The structural and morphological interpretations of the prepared nanoparticles were carried out using X-Ray Diffraction (XRD), Transmission Electron Microscopy (TEM) techniques. Optical absorption, emission properties and functional group analysis were carried out using UV-Vis, PL and FTIR techniques. The XRD results confirmed the hexagonal wurtzite crystal structure of nanoparticles with an average particle size of 17.19 nm. The anticancer ability of the prepared samples against the human liver carcinoma cell line Huh7 was investigated by studying the cell penetration, cell viability and ROS generation mechanisms.